Renal AML Surgically Treated 33 Cases - Salama, Mohamed; Mostafa, Amr; Salama, Nada; Alabrak, Mona; Abdalaleem, Shaimaa; Hanafy, Ayman (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Renal angiomyolipoma (RAML) is a rare benign neoplasm with a prevalence varying between 0.2% and 0.6% and a strong female predilection. They occur as sporadic, isolated entities in 80% of cases. The remaining 20% of angiomyolipomas (AMLs) develop in association with tuberous sclerosis complex or pulmonary lymphangioleiomyomatosis. AIM: We describe our 10-year experience with AML and discuss the treatment strategies employed at our center. METHODS: The medical records of all 33 patients with pathologically confirmed RAML treated either by nephrectomy or nephron-sparing surgery at our center over 10 years were reviewed for patient age and sex, tumor location and size, association with TBS. RESULTS: There were 28 females (84.8%) and 5 males (15.2%) with a median age that was 52 (range 22–74) years at the time of surgery. Thirty patients (90.9%) had sporadic isolated AML, and 3 patients (9.1%) had AML with TBS. The tumor was in the right kidney in 15 (45.5%) patients, in the left kidney in 17 (51.5%) patients, and bilateral in only 1 patient (3%) who was diagnosed with TBS. At presentation, flank pain was the main symptom in 23 patients (69.7%). CONCLUSIONS: Surgical resection of RAML provides short-term symptomatic relieve and long-term survival.